Giving Lavender Therapy Aroma to Dysmenorrhea Pain in Adolescents in Iloheluma Village, Patilanggio District, Pohuwato Regency - Salfa Nihe; Anik Purwati; Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Primary dysmenorrhea is menstrual discomfort that begins during menarche and is not associated with any underlying pelvic pathological disorders. It is a common condition that can significantly affect daily activities and lower the quality of life. The pain often associated with dysmenorrhea may be alleviated by improving blood circulation and utilizing pleasant aromas. One of the most widespread gynecological conditions, dysmenorrhea affects women of all ages and is frequently characterized by painful menstruation. Aromatherapy, particularly with lavender flowers, has been traditionally used to treat a variety of conditions including pain, postpartum depression, anxiety, and discomfort following cesarean sections. It has also been used to reduce dysmenorrhea. According to the World Health Organization (WHO), 90% of women experience some form of dysmenorrhea, with 10–15% of these cases classified as severe. Pain management strategies for dysmenorrhea can be categorized into pharmaceutical and non-pharmacological methods, with aromatherapy being one of the prominent non-pharmacological techniques. This study aimed to assess the impact of lavender flower aromatherapy (Lavandula angustifolia) on the severity of dysmenorrhea in teenage females residing in Iloheluma Village, Patilanggio District, Pohuwato Regency. A quantitative, quasi-experimental approach was utilized in this research, employing a purposeful sampling method. The severity of dysmenorrhea discomfort before and after the lavender aromatherapy sessions was evaluated using the paired t-test. Of the respondents, 55% were aged 15–19 years. Prior to the aromatherapy treatment, 100% of participants reported moderate pain intensity. Following the aromatherapy session, the most common pain level reported by the participants (100%) was mild pain. These results suggest that lavender flower aromatherapy has a significant effect in reducing the severity of dysmenorrhea and can be considered an effective non-pharmacological intervention for menstrual discomfort.